Cheetah skin structure: A new approach for carbon-nano-patterning of carbon nanotubes. (April 2017) - Shirvanimoghaddam, Kamyar; Abolhasani, Mohammad Mahdi; Li, Quanxiang; Khayyam, Hamid; Naebe, Minoo
Abstract: Selective localization and periodically patterning of polymer on surface of carbon nanotube (CNT) have been used as a practical approach for surface modification of CNT to overcome the poor solubility and processability of CNT in the different composites. Formation of carbon nanoparticle (CNP) on carbon nanotubes has been investigated in this research for the development of nanohybrid composites. Two distinct morphology of polyacrylonitrile (PAN) coated on CNT is observed. A novel approach to design a cheetah skin structure comprising of carbon-nano-patterning of carbon nanotubes is introduced. The cheetah skin structured CNT/CNP nanohybrid composite could lead to the development of the high-performance carbon based materials for high-tech applications in biotechnology, nano electronics and energy storage devices.